2019
DOI: 10.5688/ajpe6554
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Reflective Journal-Writing Framework for Pharmacy Students to Increase Self-Awareness and Develop Actionable Goals

Abstract: Objective. To develop and evaluate the effectiveness of a structured model for reflective journal writing (RJW) and a grading rubric as part of a student portfolio designed to help Doctor of Pharmacy (PharmD) students create actionable goals. Methods. A structured, eight-domain format was developed to engage students in prioritization, identification, exploration, recollection, evaluation, and challenging/solidifying their own knowledge, while assembling an action plan for development (abbreviated using the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…A multi-faceted approach to analysis was undertaken. It began with the student (KH) becoming familiar with reflective practice and educational outcomes for the program [30], reviewing selected literature on reflective practice and related instructional approaches in pharmacy and health sciences programs [13,16,19,20,25,[39][40][41][42], reviewing reflective practice assignments in PharmD course syllabi, discussing with the supervisor (TJS), and ruminating on personal experiences with reflective practice. As part of this phase, the first author (KH) documented an initial reflection:…”
Section: Discussionmentioning
confidence: 99%
“…A multi-faceted approach to analysis was undertaken. It began with the student (KH) becoming familiar with reflective practice and educational outcomes for the program [30], reviewing selected literature on reflective practice and related instructional approaches in pharmacy and health sciences programs [13,16,19,20,25,[39][40][41][42], reviewing reflective practice assignments in PharmD course syllabi, discussing with the supervisor (TJS), and ruminating on personal experiences with reflective practice. As part of this phase, the first author (KH) documented an initial reflection:…”
Section: Discussionmentioning
confidence: 99%
“…This strategy allows us to assess competencies in a planned and structured way [ 48 ]. On the other hand, and at the end of the PPE III and IV courses, each student will reflect on his/her culminating practical experiences by writing an essay and filling a site evaluation rubric, as well as his/her ability to assess self-awareness and personal development [ 49 , 50 ]. Examples of students’ reflective writings are presented in Table 1 .…”
Section: Competency-based Assessmentmentioning
confidence: 99%
“…This study revealed professionalization themes of development of practice skills, ability to teach others, service to the underserved, and career development. 15 Of note, Hughes and colleagues developed a seven-step structured approach to critical self-reflection for experiential, co-curricular and curricular components of their program, which planted the seed for this study adaptation to a similar but more streamlined approach suited to APPEs.…”
Section: Introductionmentioning
confidence: 99%
“…7 The aim of this article is to describe experience with the new APPE structured selfreflection process improvement and (a) determine the most impactful professionalization themes derived from student self-categorization for each APPE; and (b) analyze self-reflections for inclusion of actionable professional development plans. practices for critical self-reflection from the literature; 7,11 (c) professionalization themes of impact derived from the literature; [13][14][15] and (d) an adaptation of a 7-step reflection process from Hughes and colleagues, which had been developed to more broadly assess curricular (including APPEs) and co-curricular elements. 15 The components of the IDEA structured reflection and categorizations of themes of professionalization impact are further characterized in…”
Section: Introductionmentioning
confidence: 99%